Sistem Informasi Daya Tampung Area Parkir Pada Pusat Perbelanjaan Untuk Meningkatkan Layanan Penggunaan Parkir (Studi Kasus: Lombok Epicentrum Mall): Parking Area Resources Information System in The Shopping Center to Improve Parking Use Services (Case Study: Lombok Epicentrum Mall - Sri Endang Anjarwani; Humaira Indreswari Illina; Nadiyasari Agitha (Journal of Computer Science and Informatics Engineering (J-Cosine), 2022)
Capacity Information System Parking Area at the Shopping Center aims to facilitate customers who come to the shopping center. Regarding the increasing information needs, services such as parking services will continue to be demanded to continuously improve information systems. This is to be able to present information that is able to provide comfort, convenience and security for drivers and service managers at this time.The weakness of the regulatory system that is usually the visitor has difficulty in finding an empty parking slot, so visitors have to spin around to find the slot that is used to park their vehicles in the parking area. When you have entered the parking area, the driver does not necessarily get an empty parking space and sometimes there is no parking attendant directing to the empty area, so that the time spent looking for more parking slots. In addition, motorists usually forget where they parked their vehicles before. Therefore a system is created that is able to minimize these problems. From these problems, a Parking Capacity Information System was created that can provide convenience for service drivers and parking service personnel. The ticket is given a slot number so that it is easy to park the vehicle, the screen is provided with a map of the parking lot, and reporting is made to facilitate the management.